2001
DOI: 10.1161/hc3901.096101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Pulsed Nonablative Infrared Laser Irradiation on Vascular Cells In Vitro and Neointimal Hyperplasia in a Rabbit Balloon Injury Model

Abstract: We conclude that nonablative infrared laser inhibited neointimal hyperplasia after PTCA in cholesterol-fed rabbits for up to 60 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…[17][18][19][20][21]29,30 In the present study, we extend these findings to show that FIR radiation exerts a potent antiinflammatory effect on vascular endothelium. We observed that FIR radiation inhibits the TNF-␣-mediated expression of the adhesion molecules VCAM-1, ICAM-1, and E-selectin, as well as the chemoattractants MCP-1 and IL-8.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[17][18][19][20][21]29,30 In the present study, we extend these findings to show that FIR radiation exerts a potent antiinflammatory effect on vascular endothelium. We observed that FIR radiation inhibits the TNF-␣-mediated expression of the adhesion molecules VCAM-1, ICAM-1, and E-selectin, as well as the chemoattractants MCP-1 and IL-8.…”
Section: Discussionsupporting
confidence: 75%
“…In particular, the ability of nonablative infrared laser therapy to inhibit neointimal hyperplasia after percutaneous coronary angioplasty in hypercholesterolemic rabbits 29 may also occur through HO-1 because this enzyme protects against intimal thickening in various animal models of arterial injury. [12][13][14] In addition, the induction of HO-1 may contribute to the antioxidant effect of FIR.…”
Section: Discussionmentioning
confidence: 99%
“…61 Regarding the third mechanism, Kipshidze et al demonstrated that NIL inhibited neointimal hyperplasia. 57 Furthermore, FIR rays have been applied in treating various chronic diseases, such as hypertension, heart failure, and vascular endothelial dysfunction, which are associated with the depletion of tetrahydrobiopterin (BH4), a critical cofactor for NO synthases. 90,91 FIR therapy improves blood flow in heated surface areas, causing an increase in vascular shear stress and enhancement of the activity of GTP cyclohydrolase I, which benefits BH4 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A ké-szülék működése során a folyadékban keltett nagy sebességű áramlás hatására számos gázbuborék képződik, amelyek a nagyobb környező nyomás hatására kollabál-nak, ennek következtében az összecsapódó folyadék nagy energiájú lökéshullámot kelt (kavitáció), ami a baktériumok sejthártyáját megrongálva fejti ki baktericid hatását [25,26]. A lézerablatio keménylézerrel (erbiumdoped yttrium aluminium garnet laser -Er:YAG lézer) történő anyagelvétel, amelyet kiegészíthetünk lágyléze-res biostimulációval (diódalézerrel vagy neodymiumdoped yttrium aluminium granet laser -Nd:YAG lézer-rel), ami fokozza a sejtszaporodást, az osteoblastok szaporodását és differenciálódását, illetve az érképző-dést, amely növeli a csont és a nyálkahártya gyógyhajla-mát [27,28,29]. Használata a beteg számára kevésbé megterhelő, mivel lebenyképzést nem igényel, kevésbé fájdalmas, kevesebb vérzéssel jár [30].…”
Section: Esetismertetésunclassified